2003
DOI: 10.1183/09031936.03.00004611
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and metabolic modulation in chronic obstructive pulmonary disease management

Abstract: Nutritional and metabolic modulation in chronic obstructive pulmonary disease management. A.M.W.J. Schols. #ERS Journals Ltd 2003. ABSTRACT: In this paper the perspective for nutritional modulation of systemic impairment in patients with chronic obstructive pulmonary disease (COPD) is discussed. Progressive weight loss is characterised by disease-specific elevated energy requirements unbalanced by dietary intake. Weight gain per se can be achieved by caloric supplementation while future studies may prove effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 66 publications
2
43
0
1
Order By: Relevance
“…Ghrelin, which is released by the gastric fundus, stimulates appetite, reduces energy expenditure, enhances glucose utilization, and prevents fat consumption, thus restoring body weight and composition, both FFM and FM. 21,22 Several studies [1][2][3][4][5][6][7][8][9] have confirmed that emphysema can significantly affect glycolipidic hormones and metabolism. Insulin resistance and impaired glucose tolerance, with increased levels of insulin and HOMA-IR, but normal fasting glycemia, have been demonstrated in hypoxic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghrelin, which is released by the gastric fundus, stimulates appetite, reduces energy expenditure, enhances glucose utilization, and prevents fat consumption, thus restoring body weight and composition, both FFM and FM. 21,22 Several studies [1][2][3][4][5][6][7][8][9] have confirmed that emphysema can significantly affect glycolipidic hormones and metabolism. Insulin resistance and impaired glucose tolerance, with increased levels of insulin and HOMA-IR, but normal fasting glycemia, have been demonstrated in hypoxic patients.…”
Section: Discussionmentioning
confidence: 99%
“…ulmonary emphysema causes significant systemic alterations including progressive tissue depletion, both fat mass (FM) and fat-free mass (FFM), [1][2][3][4] mainly due to persistent inflammation, chronic hypoxemia, and impaired respiratory dynamics. The so-called respiratory cachexia is associated with the elevation of inflammatory cytokine levels and the reduction of anabolic hormone levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous strategies designed to attenuate muscle atrophy such as the use of nutritional supplements, recombinant human growth hormone, anabolic steroids and appetite stimulants (Burdet et al 1997;Creutzberg et al 2003;Schols 2003;Steiner et al 2003;Weisberg et al 2002). Positive effects of these applications have been reported including weight gain and improvements in quality of life, however none of the aforementioned strategies have reported improvements in whole body exercise performance.…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 99%
“…Another factor is that cachexia itself leads to anorexia [22], and this must create a vicious circle, such that the more weight lost, the less food is taken in. Aggressive nutritional augmentation and appetite stimulation have not solved the problem [10,23,24], casting some doubt on the centrality of this mechanism. CREUTZBERG et al [25] found that poor responders to nutritional therapy were somewhat older, had less appetite and evidence of more inflammation.…”
Section: Energy Imbalancementioning
confidence: 99%